Efektivitas Fungsi Pengawasan DPR di Tengah Dominasi Koalisi Gemuk - Farabi, Muhammad Fawwaz Farhan; Shadr, Muhammad Bagir; Khalis, Irfan; Intan, Nurul; Hanafi, Muhammad Akbar (UI Scholars Hub, 2025)
This study examines the phenomenon of oversized coalitions in Indonesian politics and their impact on the legislative role in exercising oversight over the executive branch. In a democratic context, the presence of large coalitions in parliament is often associated with a diminished balance between the legislative and executive branches, particularly concerning the essential mechanism of checks and balances. The primary issue investigated is how this political configuration affects the effectiveness of parliamentary oversight, specifically regarding the monitoring of public policy implementation and government accountability. By employing a normative legal approach and analyzing specific public policy implementations, this research assesses the impact of oversized coalitions on the legislative body's capacity to perform its functions optimally. The findings indicate challenges in achieving effective oversight within an oversized coalitions system, particularly concerning the limited role of the opposition, which is crucial for strengthening the democratic process.